Identification of human tau-tubulin kinase 1 inhibitors: an integrated e-pharmacophore-based virtual screening and molecular dynamics simulation - Jana S.; Singh S.K. (My University, 2025)
Tau-tubulin kinase 1 inhibitors inhibit tau protein phosphorylation on Ser198, Ser199, Ser202, Ser422, and also in paired helical filaments. We developed receptor-based pharmacophore models by exploiting three TTBK1 protein structures, i.e., 4NFN, 4BTM, and 4BTK. The integrated e-pharmacophore based virtual screening and molecular dynamics simulation recognized four hits viz. ZINC14644839, ZINC00012956, ZINC91332506, and ZINC69775110 as TTBK1 inhibitors. The Glide XP docking energies (−8.48 to −10.71 kcal.mol−1) of hits were better than cocrystal ligand of 4NFN protein structure (−8.37 kcal.mol−1). Among the hits, ZINC14644839 possessed best binding energy with four hydrogen bonding interactions. The inhibitors showed acceptable calculated ADME and blood-brain barrier permeability properties and could be potential TTBK1 inhibitors for neurodegenerative diseases. Communicated by Ramaswamy H. Sarma. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.